A MATHEMATICAL MODEL OF DIAGNOSING CORONARY HEART DISEASE BY MEANS OF MULTIPLE DISCRIMINATE ANALYSIS - E. A. Kuznetsov; M. A. Negasheva; V. N. Anohin; N. A. Volov; E. D. Li; O. P. Bychkova (Российский кардиологический журнал)
We have created a mathematical model of diagnozing Coronary Heart Disease by means of multifactorial discriminate analysis of objectibe biological data (laboratory and non-invasive measurements, anthropometric data) if subjective data (complaints, history, non-formalized medical interpretation), traditionally used in diagnosing the disease, are present. We have proved the model to be highly sensitive and reliable, applying it to a group of patients with CHD morphologically verified by means of angiography.